Glomerular-Bowman’s Space Correlation in Obese Rats Treated with Citrus amblycarpa Extract - Lena Rosida; Roselina Panghiyangani; Maria Ulfah; Dewi Indah Noviana Pratiwi; Siti Wasilah; Ika Kustiyah Oktaviyanti; Juliyatin Putri Utami; Rizki Aprian; Andi Muthia Azizah Tenri Bali (Global Medical & Health Communication (GMHC), 2026)
Obesity induces pro-inflammatory fat accumulation that impairs renal function, causing structural damage to the glomerulus and Bowman’s capsule. The anti-inflammatory properties of Citrus amblycarpa Hassk peel extract indicate its potential therapeutic role for these renal disorders. This study aimed to investigate the correlation between histological alterations in glomerular diameter and Bowman’s capsule width in high-fat diet-treated rats. The study used a post test control group. We divided rats into 6 groups: the normal diet (ND) group, the high-fat diet (HFD) group with orlistat, and groups receiving various doses of Citrus amblycarpa Hassk. Peels extract 200, 300, and 400 mg/kgBW. Hematoxylin and eosin (HE) stain was used for renal histological preparations. Glomerular diameter and Bowman’s capsule width were measured using a light microscope equipped with Optilab Viewer software (five microscopic fields). Glomerulus diameter was averaged from two outer-edge measurements, while Bowman’s capsule width was recorded at its widest point. Data were analyzed using Pearson’s correlation test to assess variable relationships. The mean glomerular (µm) of K1 = 89.99±5.68, K2 = 97.56±4.03, K3 = 89.99±3.91, K4 = 90.80±3.88, K5 = 86.09±4.22, K6 = 82.89±2.50 and mean Bowman’s capsule width (µm) K1 = 14.18±4.27, K2 = 9.98±2.24, K3 = 10.12±0.58, K4 = 8.87±2.85, K5 = 14.87±6.42, K6 = 15.39±4.21. The results demonstrated a significant negative correlation between increased glomerular diameter and reduced Bowman's capsule width in all experimental groups (p=0.018, r=−0.430), suggesting that glomerular enlargement is linked to structural shrinkage of the Bowman's capsule. In conclusion, a significant correlation exists between glomerular diameter changes and Bowman’s capsule width in high-fat diet rats treated with Citrus amblycarpa Hassk peel extract.